WORKED EXAMPLE USING ILL-STRUCTURED PROBLEM: TRAINED HIGH ORDER THINKING SKILL - Atik Rodiawati (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Cognitive Load Theory (CLT) is design theory instructional that uses human cognitive architecture. One of the cognitive load theory types is worked example. This study aims to analyze theoretically the ability of worked example using ill-structured problem in training high order thinking skill. This article is designed by reviewing literatures of worked example, ill-structured problem, and high order thinking skill; arranging them to get their primary relation; finally concluding the aim of this study. The main relation of them is one characteristic of high order thinking skill is ill-structured and challenging problems. The result of this research shows theoretically that worked example using ill-structured problems can train high order thinking skill. It is caused by worked example which contains ill-structured problems can train students to analyze and evaluate problem solving through examples without high cognitive load, so that students obtain ill-structured problems solving strategy. Furthermore, giving a wider problem to students' practice as a follow-up action from worked example will train students to create innovative solutions to wider problems.